Gating function of isoleucine‐116 in TM‐3 (position III:16/3.40) for the activity state of the CC‐chemokine receptor 5 (CCR5). (March 2014) - Steen, A; Sparre‐Ulrich, A H; Thiele, S; Guo, D; Frimurer, T M; Rosenkilde, M M
<x xml:space="preserve">Abstract</x> Background and Purpose A conserved amino acid within a protein family indicates a significance of the residue. In the centre of transmembrane helix (TM)‐5, position V:13/5.47, an aromatic amino acid is conserved among class A 7TM receptors. However, in 37% of chemokine receptors – a subgroup of 7TM receptors – it is a leucine indicating an altered function. Here, we describe the significance of this position and its possible interaction with TM‐3 for CCR5 activity. Experimental Approach The effects of [L203F]‐CCR5 in TM‐5 (position V:13/5.47), [I116A]‐CCR5 in TM‐3 (III:16/3.40) and [L203F;G286F]‐CCR5 (V:13/5.47;VII:09/7.42) were determined in G‐protein‐ and β‐arrestin‐coupled signalling. Computational modelling monitored changes in amino acid conformation. Key Results [L203F]‐CCR5 increased the basal level of G‐protein coupling (20–70% of Emax) and β‐arrestin recruitment (50% of Emax) with a threefold increase in agonist potency. In silico, [I116A]‐CCR5 switched χ1‐angle in [L203F]‐CCR5. Furthermore, [I116A]‐CCR5 was constitutively active to a similar degree as [L203F]‐CCR5. Tyr244 in TM‐6 (VI:09/6.44) moved towards TM‐5 in silico, consistent with its previously shown function for CCR5 activation. On [L203F;G286F]‐CCR5 the antagonist aplaviroc was converted to a superagonist. Conclusions and Implications The results imply that an aromatic amino acid in the centre of TM‐5 controls the level of receptor activity. Furthermore, Ile116 acts as a gate for the movement of Tyr244 towards TM‐5 in the active state, a mechanism proposed previously for the β2‐adrenoceptor. The results provide an understanding of chemokine receptor function and thereby information for the development of biased and non‐biased antagonists and inverse agonists.